2023
DOI: 10.1007/s40122-023-00488-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Doses of Esketamine on Pain Sensitivity of Patients Undergoing Thyroidectomy: A Randomized Controlled Trial

Abstract: Introduction Several factors may lead to increased postoperative pain sensitivity, of which remifentanil-induced hyperalgesia (RIH) is one of the main factors. High-dose remifentanil exposure during anesthesia may induce RIH. Esketamine may prevent RIH by antagonizing N -methyl- d -aspartate (NMDA) receptors, thereby reducing the postoperative pain sensitivity. This study examined the effects of different esketamine doses on pain sensitivity in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…We identified higher use doses of remifentanil as a risk factor for more intense post-operative pain, which aligns with previous research (Chen et al, 2023). Reasons may be that its use was not only associated with longer operative time but also with a rise in pain sensitivity following the use of remifentanil during surgery (Ren et al, 2023). Drainage tubes are routinely placed in most procedures to prevent fluid collection and timely find complications after surgery (Abu et al, 2022).…”
Section: Surgical Related Factors: Consumption Of Intraoperative Remi...supporting
confidence: 81%
“…We identified higher use doses of remifentanil as a risk factor for more intense post-operative pain, which aligns with previous research (Chen et al, 2023). Reasons may be that its use was not only associated with longer operative time but also with a rise in pain sensitivity following the use of remifentanil during surgery (Ren et al, 2023). Drainage tubes are routinely placed in most procedures to prevent fluid collection and timely find complications after surgery (Abu et al, 2022).…”
Section: Surgical Related Factors: Consumption Of Intraoperative Remi...supporting
confidence: 81%
“…6,9 Esketamine, the dextro-isomer of ketamine, has approximately twice the affinity for NMDAR as ketamine and is characterized by quicker onset, faster elimination, fewer adverse effects, and better sedative and analgesic potency. 10,11 Previous clinical studies have demonstrated that intraoperative esketamine application decreases early pain scores, [12][13][14] spares opioids, 15,16 reduces hyperalgesia, 17,18 and promotes postoperative recovery in various ways. [19][20][21][22][23][24] Quantitative studies on the change in the BIS caused by continuous esketamine infusion during general anesthesia are currently lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Esketamine and ketamine can deliver analgosedation action, but some drawbacks such as the induction of frequent vomiting and clustered psychiatric symptoms limit their single administration ( Nakao et al, 2003 ). Low-dose esketamine as an adjuvant has been shown to have several benefits for sedation or anesthesia, including stabilizing hemodynamics and respiratory function, decreasing propofol requirements, or reducing postoperative pain sensitivity ( Huang et al, 2023 ; Ren et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%